GEOGRAPHIC DIFFERENCES IN THE RISK OF SURGERY IN INFLAMMATORY BOWEL DISEASE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (22nd January 2022) - Hansen, Tawnya; Mak, Joyce; Underwood, Fox; Windsor, Joseph; King, James; Quan, Joshua; Buie, Michael; Coward, Stephanie; Frolkis, Alex; Leung, Alexander; Ma, Christopher; Novak, Kerri; et al.
Abstract: BACKGROUND: The management of inflammatory bowel disease (IBD) is associated with considerable healthcare and societal cost. A key driver of direct medical cost, remains surgery. Although the cumulative risks of surgery have been well described in countries of the Western world, surgical risk data from Asia, where IBD is rapidly emerging, is lacking. OBJECTIVES: The primary objective was to compare the cumulative risk of surgery at 1-year after a diagnosis of Crohn's disease (CD) and ulcerative colitis (UC) between contemporary adult population-based cohorts from the Western world and Asia. Secondarily, we estimated 5- and 10-year risks of IBD-related surgery. METHODS: MEDLINE and EMBASE were searched for population-based studies published on or after January 1, 2000, that reported 1-, 5-, and 10-year risks of IBD-related surgery. Authors were contacted to provide previously unpublished data. Random effects models were performed to analyze temporal and regional risks of surgery for cohorts diagnosed with IBD in the year 1998 and later. RESULTS: The initial search yielded 10, 358 citations. Of those, 37 studies were used in analyses. For UC, the 1-, 5-, and 10-year risk of surgery were 1.71% (95% confidence intervals [CI]: 1.13, 2.29), 3.77% (95% CI: 2.41, 5.13), and 8.33% (95% CI: 5.03, 11.63), respectively. For CD, the 1-, 5-, and 10-year risk of surgery were 7.17% (95% CI: 5.92, 8.42), 13.63% (95% CI: 11.26, 16.00), and 24.57% (95% CI: 19.21, 29.93), respectively (Table 1; Figure 1). For CD, the 1-year risk of surgery was 7.44% (95% CI: 6.07, 8.80) and 7.22% (95% CI: 2.65, 11.78) for countries in the Western world and countries in Asia, respectively ( p = 0.93). The Western 5-year risk of CD surgery (13.52%, 95% CI: 10.85, 16.19) was similar to Asia (15.95%, 95% CI: 5.48, 26.43) ( p =0.66). The 1-year risk of surgery for UC was not significantly different between Western world countries (1.87%, 95% CI: 1.27, 2.47) and Asia (0.74%, 95% CI: -0.48, 1.97) ( p =0.13). The pooled 5-year risk of surgery was significantly higher in countries of the Western world (4.13%, 95% CI: 2.71, 5.55) as compared to Asia (2.11%, 95% CI: 1.88, 2.33) ( p =0.02). Comparison of pooled 10-year risk between countries of the Western world and Asia was not possible as there was only one Asian study published on risk of surgery 10-years after CD and UC diagnosis each. CONCLUSIONS: During the 21 st century the risk of early surgery 1-year after the diagnosis for CD and UC was similar in countries of the Western world as compared to Asia. Long-term (10-year data) was lacking for Asian countries. Future studies are needed to generate more robust long-term estimates for risks of IBD-surgery in Asia.